Lincoln and the Patronage - Carman, Harry J. 1884-1964; Luthin, Reinhard H. 1905-1962 (Columbia University Press, 1943)
Describes the extent of Lincoln's use of patronage during his administration and the influence it had before, during, and after the Civil War